P244 COVID-19 vaccine does not increase the likelihood of disease exacerbation in IBD: results from a population-based study. (21st January 2022) - Lev Zion, R; Focht, G; Lujan, R; Mendelovici, A; Friss, C; Greenfeld, S; Kariv, R; Ben-Tov, A; Matz, E; Nevo, D; Barak-Corren, Y; Dotan, I; et al.
Abstract: Background: While short-term safety data of COVID-19 vaccination has been reassuring, it is theoretically possible that the vaccine-associated immune activation could trigger immune dysregulation and thus exacerbation of IBD. We used the epi-Israeli IBD Research Nucleus (IIRN) database to perform a population-based study exploring the effect of COVID-19 vaccination on disease course in IBD patients. Methods: We included all IBD patients insured in two of the four Israeli HMOs, covering 35% of the population, by validated algorithms, and selected those who received two doses of Pfizer BNT162b2 vaccine. These were matched to unvaccinated IBD patients by demographics, parameters of disease severity at baseline generated by hierarchical clustering of laboratory data, and length of time from previous exacerbation to baseline. The primary outcome was rate of IBD exacerbation as defined by proxies of hospitalizations, treatment escalation, and commencement of corticosteroid or enema. The study period was December, 2020 to June, 2021 Results: 707 pairs of vaccinated and unvaccinated IBD patients were compared. The pairs matched exactly for gender, district, IBD type and disease severity, and ±1 year for age at IBD diagnosis and at vaccination. Mean age was 38.5±13.5 years and median follow-up was 98 days (IQR 16–143). No difference in the outcome was found between the groups from the 2 nd vaccination to the end of follow-up, with risk of exacerbation in vaccinated patients of 29% and risk in unvaccinated patients 26% (p=0.3). Conclusion: COVID-19 vaccinated IBD patients demonstrated a rate of IBD exacerbation following vaccination that was no different from that of unvaccinated patients. The multifaceted immune activation induced by the vaccine did not result in worsening IBD disease course. These results provide further reassurance for IBD patients receiving the vaccine.